Railing, reviling, and invective in English literary culture, 1588 - 1617: the anti-poetics of theater and print - Prendergast, Maria Teresa Micaela (Material readings in early modern culture, 2012)
Introduction: railing, reviling, and invective -- The queer poetics of the Marprelate controversy -- Promiscuous parthenogeneses: the Nashe-Harvey controversy -- Theaters of envy: the poets' war and Troilus and Cressida -- Aristocratic remains: Coriolanus and Timon of Athens -- Dogges, verse, and effeminate men: the misandronic railings of anger, munda, and sharp -- Conclusion